2017
DOI: 10.1016/j.socscimed.2017.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Mental retirement and health selection: Analyses from the U.S. Health and Retirement Study

Abstract: Background Research has recently suggested that retirement may decrease cognitive engagement, resulting in cognitive aging. Few studies have systematically documented whether or how selectivity into retirement shapes the relationship between retirement and cognitive aging. Methods We draw on data from the Health and Retirement Study (1998-2012) to examine the relationship between cognition and retirement for 18,575 labor force participants. Longitudinal regression discontinuity modeling was used to examine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 58 publications
2
38
1
Order By: Relevance
“…A further limitation of these studies is their short follow-ups and use of only one measure of cognitive function. A few studies have examined change in cognitive function before and after retirement [ 22 , 35 ], but most have relatively short follow-up period [ 36 ], and thus cannot estimate the long-term effects of retirement on cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…A further limitation of these studies is their short follow-ups and use of only one measure of cognitive function. A few studies have examined change in cognitive function before and after retirement [ 22 , 35 ], but most have relatively short follow-up period [ 36 ], and thus cannot estimate the long-term effects of retirement on cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have employed a variety of solutions to try and address these methodological challenges. From studies using cross-national variation in the statutory retirement age and instrumental variable techniques, there is mixed evidence that retirement is negatively associated with health, broadly, or cognitive function, specifically (Adam et al 2013;Bonsang et al 2012;Celidoni et al 2017;Clouston and Denier 2017;Coe et al 2012;Coe and Zamarro 2011;Denier et al 2017;Mazzonna and Peracchi 2012;Rohwedder and Willis 2010). For example, using the HRS and ordinary least squares regression, Coe and colleagues (2012) find retirement is associated with lower cognitive function.…”
Section: ; Mehta and Preston 2016)mentioning
confidence: 99%
“…However, when they use time between interview and offer of early retirement as an instrument, they find no negative causal effect of retirement on cognitive function for white-collar workers and a slight positive effect for blue-collar workers. In contrast, Clouston and Denier (2017) and Bonsang and colleagues (2012), respectively, use longitudinal regression discontinuity models and eligibility for social security as an instrument.…”
Section: ; Mehta and Preston 2016)mentioning
confidence: 99%
“…It is important to note that there are multiple definitions of retirement in the literature (e.g., Denton & Spencer, 2009;Ekerdt, 2010;Wang & Shi, 2014) and that the transition to retirement does not always reflect a discrete process. The present study defines retirement using a simple but common approach based on participant perceptions of whether they were retired (i.e., whether participants self-reported that they were retired) (see, for example, Clouston & Denier, 2017;Bonsang et al, 2012;Fisher et al, 2014;Wickrama et al, 2013).…”
Section: Definition and Operationalization Of Retirementmentioning
confidence: 99%